2021
DOI: 10.1172/jci.insight.146314
|View full text |Cite
|
Sign up to set email alerts
|

TNF blockade uncouples toxicity from antitumor efficacy induced with CD40 chemoimmunotherapy

Abstract: Agonist CD40 antibodies are under clinical development in combination with chemotherapy as an approach to prime for anti-tumor T cell immunity. However, treatment with anti-CD40 is commonly accompanied by both systemic cytokine release and liver transaminase elevations which together account for the most common dose-limiting toxicities. Moreover, anti-CD40 treatment increases the potential for chemotherapy-induced hepatotoxicity. Here, we report a mechanistic link between cytokine release and hepatotoxicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Depleting macrophages or neutrophils or blocking TNFα production was sufficient to prevent anti-CD40 induced liver damage, which is consistent with previous reports. 41 , 53 , 54 , 55 , 56 Our study adds to these previous reports by demonstrating that the gut microbiota is critically required for anti-CD40-induced pathogenic immune cell infiltration/activation in the liver and for anti-CD40-induced cytokine release. While both macrophages and neutrophils were required for anti-CD40-induced liver damage, only macrophage depletion reduced anti-CD40-induced systemic TNFα release.…”
Section: Discussionsupporting
confidence: 56%
“…Depleting macrophages or neutrophils or blocking TNFα production was sufficient to prevent anti-CD40 induced liver damage, which is consistent with previous reports. 41 , 53 , 54 , 55 , 56 Our study adds to these previous reports by demonstrating that the gut microbiota is critically required for anti-CD40-induced pathogenic immune cell infiltration/activation in the liver and for anti-CD40-induced cytokine release. While both macrophages and neutrophils were required for anti-CD40-induced liver damage, only macrophage depletion reduced anti-CD40-induced systemic TNFα release.…”
Section: Discussionsupporting
confidence: 56%
“…S2, D and E). In addition, combination treatment showed no evidence of increased rates of cytokine release syndrome or hepatotoxicity ( 30 ), which are common adverse events with aCD40 (fig. S2, F and G).…”
Section: Resultsmentioning
confidence: 99%
“…BE0016-2; RRID: AB_1107647; 0.1 mg) was administered on day 0. Mice (~5%) that did not show depletion of CD19 + B cells at 24 hours after treatment with anti-CD40 were excluded as previously described ( 30 ). For T cell depletion, anti-CD4 (clone GK1.5; catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, it is worth mentioning that preclinical studies have shown that the intratumoral and systemic application of anti-CD40 antibodies is therapeutically equally effective, but that local application in the tumor is associated with fewer side effects [ 105 , 106 , 107 , 108 , 109 ]. Moreover, a recent study showed that TNF inhibition prevented the hepatotoxicity triggered by combined treatment with an anti-CD40 antibody and gemcitabine without affecting antitumor activity [ 110 ]. Thus, the maximal exploitation of potent autonomous CD40 agonists for tumor therapy may require defined treatment regimens that restrict the antibody activity to the tumor area and/or systemically inhibit CD40 effector molecules.…”
Section: Cd40 As Therapeutic Targetmentioning
confidence: 99%